Assessing maternal clotting function with novel global coagulation assays: A prospective pilot study. (10th November 2020) - O'Keefe, David; Lim, Hui Yin; Tham, Johnathan; Ho, Prahlad; Hui, Lisa
Abstract: Introduction: Women are at higher risk of venous thromboembolism (VTE) during pregnancy and the puerperium. Global coagulation assays (GCAs), including thromboelastography (TEG), thrombin generation using the calibrated automated thrombogram (CAT) and fibrin generation using the overall haemostatic potential assay (OHP), provide a more comprehensive assessment of the coagulation process than conventional coagulation assays. We aimed to evaluate the ability of these GCAs to analyse the coagulability among pregnant women of varying VTE risk profile. Methods: Women undergoing term elective caesarean delivery provided a single predelivery blood sample for conventional and novel coagulation testing (TEG, CAT and OHP). Data from 47 healthy nonpregnant women aged 18‐45 years were used as controls. Results: Sixty women with term singleton pregnancies were included. Samples from pregnant women were hypercoagulable on most GCA parameters compared to nonpregnant controls, demonstrating increased maximum amplitude (clot strength) (71.5 vs 60.6 mm, P < .001) on whole blood TEG and increased endogenous thrombin potential (1895.22 vs 1399.33 nmol/L·min, P < .001) and overall coagulation potential (fibrin generation) (57.58 vs 36.21 units, P < .001) on platelet‐poor plasma. Pregnant women with booking BMI ≥ 30 kg/m 2 had significantly higher maximum amplitude compared to pregnant women of normal BMI (18.5‐25 kg/m 2 ) (73.2 vs 66.1 mm, P < .001). Conclusions: Global coagulation assays reliably detect the physiological hypercoagulability of pregnancy. Thromboelastography in particular appears to correlate with obesity in the pregnant population. GCAs may be potential adjuncts to risk factor‐based criteria to guide VTE thromboprophylaxis during pregnancy and the puerperium.